An introduction to systems science - Warfield, John N; Warfield, John N (World Scientific Publishing Co. Pte. Ltd, 2006)
This is the first book that renders a thorough discussion of systems science. It draws on material from an extensive collection of external sources, including several other books and a special library collection complete with videotape empirical evidence of applicability of the theory to a wide variety of circumstances. This is essential because systems science must be responsive to diverse human situations of the widest difficulty, and it must fill the void that the specific sciences cannot fill, because these sciences are insensitive to the necessities of reconciling disparate views of multiple observers, and incorporating local conditions in hypotheses that precede inductive explorations.